Slow Growing Desmoid-Type Fibromatosis of the Breast: A Case Report - Park, Ah Reum; Kim, Ji-Young; Kim, Hyun Jung; Kim, Jae Hyung; Jeong, Myeong Ja; Kim, Soung Hee; Kim, Soo Hyun; Kang, Mi Jin; Lee, Ji Hae; Bae, Kyung Eun (Journal of the Korean Society of Radiology, 2017)
Fibromatosis or desmoid tumor of the breast is a rare benign entity that has no metastatic potential but has significant risk of local recurrence. Its association with previous surgical or accidental trauma and Gardner's syndrome has been reported. Awareness of this lesion is important as the diagnosis is often confused with breast carcinoma. We report a case of a 44-year-old woman who presented with a palpable mass in her left breast, close to the axilla since a few months ago. She had undergone excisional biopsy for her left breast mass 15 months ago, and the diagnosis was confirmed as intraductal papilloma with atypical ductal hyperplasia. Subsequent ultrasound and core needle biopsy revealed stromal fibrosis. After 9 months, the mass showed an increase in its size and the anteroposterior to width ratio on ultrasonography compared to the previous examination, and final excisional biopsy confirmed the diagnosis of desmoid-type fibromatosis.